Pengaruh Miskonsepsi Dan Polusi Informasi Dalam Citayam Fashion Week Menurut Filsafat Das Sein Martin Heidegger - Fransesco Agnes Ranubaya; Adrianus Koban; Yohanes Endi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
The purpose of this research is first to make people aware, especially young people, so that through the Citayam Fashion Week phenomenon, they are able to provide an understanding of fair content in the digital world according to the correct concept. Second, viralism that is too free on social media as happened in Citayam Fashion Week can stifle the right reason and knowledge so that it requires the right concept knowledge. The focus of this research is to systematically review how the forms of misconceptions and information pollution according to the ethics of digital communication are based on the review of Martin Heidegger's thoughts on the existence of today's humans as the future Das Man, namely Digi-sein. The research method of this scientific paper uses critical analysis through a study of the approach to documents. The flow of discussion in this study reviews the definition of misconception, the concept of das Man Martin Heidegger, information pollution, reviews the Citayam Fashion Week phenomenon to critically reviews problems according to the ethics of digital communication based on a review of Martin Heidegger's thoughts. The findings of this study include the effects of misconceptions and information pollution in Citayam Fashion Week that have the potential to harm young people and describe in detail the forms of misconceptions and information pollution as knowledge to anticipate negative impacts on society, especially young people. This research is very relevant to the current situation, especially in the digital world, so it is hoped that both content creators and young people as citizens will be able to become ethical and responsible digital actors.